Effect of hypolipidemic treatment on glycemic profile in patients with mixed dyslipidemia - Kei, Anastazia (Baishideng Publishing Group Co., Limited, 2013)
AIM: To assess the effect of different hypolipidemic treatment strategies on glycemic profile in mixed dyslipidemia patients. METHODS: This is a prespecified analysis of a prospective, randomized, open-label, blinded end point (PROBE) study (ClinicalTrials.gov identifier: NCT01010516). Patients (n = 100) with mixed dyslipidemia on a standard statin dose who had not achieved lipid targets were randomized to switch to the highest dose of rosuvastatin (40 mg/d) or to add-on-statin extended release nicotinic acid (ER-NA)/laropiprant (LRPT) or to add-on-statin micronised fenofibrate for a total of 3 mo. Fasting plasma glucose (FPG), glycosylated hemoglobin (HbA1c), homeostasis model assessment of insulin resistance (HOMA-IR) index and lipid profile were evaluated at baseline and 3 mo after treatment intervention. RESULTS: FPG increased in add-on ER-NA/LRPT and rosuvastatin monotherapy groups by 9.7% and 4.4%, respectively (P < 0.01 between the 2 groups and compared with baseline), while it did not significantly change in the add-on fenofibrate group. Similarly, HbA1c increased by 0.3% in add-on ER-NA/LRPT group and by 0.2% in the rosuvastatin monotherapy group (P < 0.01 for all comparisons vs baseline and for the comparison between the 2 groups), while no significant change was reported in the add-on fenofibrate group. HOMA-IR increased by 65% in add-on ER-NA/LRPT and by 14% in rosuvastatin monotherapy group, while it decreased by 6% in the add-on fenofibrate group (P < 0.01 vs baseline and for all comparisons among the groups). Non-HDL-C decreased in all groups (by 23.7%, 24.7% and 7% in the rosuvastatin, ER-NA/LRPT and fenofibrate group, respectively, P < 0.01 for all vs baseline and P < 0.01 for all vs with fenofibrate group). CONCLUSION: Both addition of ER-NA/LRPT and switch to the highest dose of rosuvastatin deteriorated glycemic profile in patients with mixed dyslipidemia, while add-on fenofibrate seems to increase insulin sensitivity.